River Boundary Delineation under PUPR Regulation 28/PRT/M/2015 Land Ownership Implications - Nurani Cipta Putri; Tunggul Anshari Setia Negara; Dewi Cahyandari (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
The research gap addressed in this study lies in the limited scholarship integrating the implementation of river boundary delineation with legal protection of land ownership rights through a comprehensive normative and empirical approach. This study aims to analyze the implementation of river boundary delineation under the Regulation of the Minister of Public Works and Housing Number 28/PRT/M/2015 concerning Land Ownership Rights and to examine the forms of legal protection available to affected landowners. The research employs a socio-legal method, incorporating statutory, sociological, and case approaches. Primary data were collected through interviews, while secondary data consisted of legal materials and relevant literature. The data were analyzed qualitatively using grammatical, systematic, and constructive interpretation. The findings indicate that river boundary delineation is supported by a valid legal basis of authority; however, its implementation continues to face significant challenges, including inconsistencies between land administration and spatial planning data, discrepancies between factual land occupation and juridical ownership, and weak inter-agency coordination. These issues ultimately create legal uncertainty for holders of land ownership rights. Based on these findings, the novelty of this study lies in proposing a legal protection model that integrates the harmonization of land administration and spatial planning data, strengthens institutional coordination, and establishes administrative mechanisms capable of ensuring legal certainty for certified land located within river boundary areas without compromising the ecological functions of rivers.